Phospholipids and a phospholipid-rich diet alter the in vitro amyloid-beta peptide levels and amyloid-beta 42/40 ratios - Amtul, Zareen; Uhrig, Markus; Supino, Rosanna; Beyreuther, Konrad (Neuroscience letters, 2010)
Amyloid-β peptides (Aβ) generated by proteolysis of the β-amyloid precursor protein (APP) by β- and γ-secretases play an important role in the pathogenesis of Alzheimer's disease (AD). There is mounting evidence that the lipid matrix of neuronal cell membranes plays an important role in the accumulation of Aβ peptides into senile plaques, one of the hallmarks of AD. With the aim to clarify the molecular basis of the interaction between Aβ and cellular membranes, we investigated the effects of various phospholipids (PLs) and a PL-rich diet on Aβ production. Here we show that modulation of Aβ production and Aβ42:40 ratio is not limited to individual fatty acids, rather it is the composition of the PLs of the membrane bilayer, that influences the specificity and level of the regulated intramembranous proteolysis of APP by the γ-secretase complex. We show that Aβ levels in the conditioned media, in response to some of the PL supplements, is increased in the center and decreased on either side of a graph that resembles bell-shaped distribution. This means that the PLs have less of a tendency to produce unusually extreme effects on Aβ production in SP-C99 transfected Cos-7 cultured cells. We proposed a mechanism-based hypothesis to rationalize PLs’ effects on Aβ production.